2006
DOI: 10.1128/iai.74.4.2187-2195.2006
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Independent, Interleukin-17A-Mediated, Cross-Serotype Immunity to Pneumococci in Mice Immunized Intranasally with the Cell Wall Polysaccharide

Abstract: Serotype-specific immunity to Streptococcus pneumoniae is conferred by antibodies to the capsular polysaccharides, which define the 90 known serotypes. Whether antibody to the species-common cell wall polysaccharide (C-Ps) is protective has been a matter of controversy. Here we show that C-Ps given intranasally with mucosal adjuvant increased the resistance of mice to experimental nasopharyngeal colonization by capsulated S. pneumoniae of serotype 6B. This immunity could be induced in mice congenitally lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
138
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(147 citation statements)
references
References 60 publications
6
138
0
3
Order By: Relevance
“…For instance, CD4 + T cell-derived IL-17A has been shown to protect vaccinated animals from colonization with Streptococcus pneumoniae (49). However, in some reports the distinct roles of IL-17A in nonvaccinated versus vaccinated mice have been poorly defined and it remains obscure to what extent IL-17A was produced by cells of the innate or the adaptive immune system (22,23,50). Our results show that IL-17A has no effect on the clearance of S.flexneri on primary infection, consistently with its low production during the innate response.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, CD4 + T cell-derived IL-17A has been shown to protect vaccinated animals from colonization with Streptococcus pneumoniae (49). However, in some reports the distinct roles of IL-17A in nonvaccinated versus vaccinated mice have been poorly defined and it remains obscure to what extent IL-17A was produced by cells of the innate or the adaptive immune system (22,23,50). Our results show that IL-17A has no effect on the clearance of S.flexneri on primary infection, consistently with its low production during the innate response.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we and colleagues are attempting also to devise biochemically defined pneumococcal constructs with a similar bifunctional potential. The cell wall polysaccharide (CWPS) of pneumococcus (structurally, a teichoic acid) is a highly conserved, serotype-independent antigen with a zwitterionic structure that confers the capacity for T cell activation and IL-17A elicitation (69)(70)(71)(72). Administered i.n.…”
Section: Noncapsular Components As Immunogensmentioning
confidence: 99%
“…Administered i.n. to mice as a stand-alone antigen, CWPS induces IL-17A-mediated clearance of pneumococci similarly to WCA (72,73). Noting this feature, the work by Lu et al (73,75) coupled CWPS to a fusion protein, combining portions of the protein pneumococcal surface adhesin A (known to induce resistance to colonization) and a genetically detoxified variant of the cholesterol-dependent toxin pneumolysin (known to induce protection against systemic toxic effects of pneumococcus as well as be a TLR4 agonist) (74).…”
Section: Noncapsular Components As Immunogensmentioning
confidence: 99%
“…It was shown that although Th17 cells are not critical to the primary response to M. tuberculosis, Th17 activation is clearly involved in response to vaccination against tuberculosis (Khader et al 2007). In addition to this Th17-mediated vaccine-induced immunity to M. tuberculosis, Th17 cytokine responses have also been implicated in vaccineinduced immunity against B. pertussis and Streptococcus pneumoniae (Malley et al 2006). This indicates that the host Th17 effector cytokines have evolved as protective immune mechanisms against extracellular bacteria but are dispensable for primary protection against most intracellular pathogens that require a Th1 pathway for protection, such as in tuberculosis infection.…”
Section: Bacteriamentioning
confidence: 99%